Impact of CLIL on Scientific English and Problem-Solving Skills: A Quasi-Experimental Study in Moroccan Middle Schools - Bendraou, Rachid (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study examines how CLIL (Content and Language Integrated Learning) can scaffold Moroccan school students to enhance their scientific English and problem-solving skills. This is important as it integrates language learning with subject mastery, a concept increasingly valued in academia and critical thinking development. The study employed a one-group pre-test and post-test design, with 25 middle school students participating in a science-oriented CLIL intervention. The results of a paired t-test revealed a significant improvement in scientific English proficiency and problem-solving ability following completion of the course. Compared to pre-test scores, post-test scores had increased considerably, concluding that the CLIL technique helped students acquire desirable academic skills (M difference = -5.640, SD = 3.303, SE = 0.661, t (24) = -8.539, p = 0.000), with a 95% confidence interval of [-7.003, -4.277]. This finding directly contributes to the ongoing efforts in Morocco to transform language and content instruction. It demonstrates that CLIL can significantly enhance learning outcomes, offering a pathway to improving the quality of teaching and learning in Moroccan schools.